HUBUNGAN MEDIA ELEKTRONIK DENGAN PERILAKU SISWA TENTANG SEKS PRA-NIKAH DI SMK MUHAMMADIYAH 2 KOTA PEMATANGSIANTAR TAHUN 2012 - Utari * (Kebijakan, Promosi Kesehatan dan Biostatiskik, 2012)
In the globalization era, the flows of information from western countries are so rapid, like the sophisticated electronic media. The positive effect of this current technological development is information in this world can be accessed in very short time. This condition can certainly cause a vulnerable and dangerous situation in the sexual behavior of teenagers, especially about premarital sex. This research is descriptive analytic based on cross sectional design. The sample is selected by total sampling with inclusion and exclusion criteria. The population in this study were 93 people with the sample in this study amounted to 76 people. The primary data obtained by using questionnaire. This research used Fisher’s Extract Test with the results of this research showed that the knowledge of respondents about premarital sex are mostly located in the medium category (56,6%), the attitudes of respondents about premarital sex mostly in medium category (59,2%), and the action of respondents about premarital sex are mostly located in the medium category (64,5%). There is a significant relationship between the electronic media with the knowledge (0,046), attitude (0,022), and action (0,022) of the respondent about premarital sex. Based on the results of this research, SMK Muhammadiyah 2 Pematangsiantar should make collaboration with related parties to make counseling on sex education to students about premarital sex, and is expected to the students to improve their knowledge, attitude and action on premarital sex.